Pembelajaran Efektif Model SSIP 2000: Tahap Pengembangan Modul - Wahyuningsih, Sri; Kartika, Aniva (ANIMA Indonesian Psychological Journal, 2002)
Basic education in Indonesia is considered incapable to lead the students to meet their optimal performance. Students are not actively involved in the learning process; the process as well as the learning material are not interesting due to the lack of correlation with the daily life activities, needs, and life experiences of the students. Based on these situations, an improvement in education leading towards quality enhancement is urgent. Correlating content and learning process with student needs and experience, and concentrating learning activities on students and enlargement of learning domains are needed. Sidoarjo School Improvement Programme 2000 (SSIP 2000) was programmed with the aim to enhance the quality of learning sistematically based on (a) Rosenshine's direct instruction, (b) learning process improvement, replacing instructional teaching into interactional learning, from teacher centred to student centred learning. SSIP 2000 was implemented through 3 phases: development, implementation, and evaluation of the learning package. Positive as well as negative experiences obtained by the Learning Development Package Team are discussed.